2019
DOI: 10.1016/j.ijpara.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A library of recombinant Babesia microti cell surface and secreted proteins for diagnostics discovery and reverse vaccinology

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 52 publications
1
25
0
1
Order By: Relevance
“…Amino acid sequence alignment analysis revealed that 03g04550 was similar to the secreted antigens from Plasmodium falciparum and Babesia bovis (unpublished data). This result was consistent with previous reports from Elton et al (2019).…”
Section: Anti-bmsa1 Antiserum Inhibits Merozoite Invasionsupporting
confidence: 94%
“…Amino acid sequence alignment analysis revealed that 03g04550 was similar to the secreted antigens from Plasmodium falciparum and Babesia bovis (unpublished data). This result was consistent with previous reports from Elton et al (2019).…”
Section: Anti-bmsa1 Antiserum Inhibits Merozoite Invasionsupporting
confidence: 94%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ subsequent boosters, respectively. Sera were harvested from tail bleeds of immunised mice 8 days after the final immunisation, with antibody titres determined using ELISA as previously described 66 . Briefly, a fixed concentration of the biotinylated control protein was immobilised on 96-well streptavidin plates (Thermo Scientific) and incubated with serial dilutions of the corresponding sera prepared in HBS/0.1% (v/v) Tween 20 (HBST), containing 2% (w/v) BSA.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, structures such as the Maurer’s clefts and the tubulovesicular network, previously shown to be present in the cytoplasm of Plasmodium falciparum –infected erythrocytes, are not found in B. microti –infected erythrocytes (Marti et al, 2005; Lanzer et al, 2006; Pelle et al, 2015; Cornillot et al, 2016; de Koning-Ward et al, 2016; Sherling & van Ooij, 2016). Proteomic, immunoproteomic, and genomic efforts used to search for major antigens of the parasite, which could be used as vaccines or diagnostic biomarkers, identified several antigens of B. microti that trigger a strong host immune response in mice and humans (Molestina et al, 2002; Cornillot et al, 2016; Silva et al, 2016; Elton et al, 2018). Among these, BmGPI12 (BmSA1) has been shown to trigger the strongest IgM and IgG responses and has been successfully used as a diagnostic marker of active B. microti infection (Thekkiniath et al, 2018).…”
Section: Introductionmentioning
confidence: 99%